Training on Making Virgin Coconut Oil (VCO) by Acidification Method in Gampong Lambro Deyah, Kuta Baro District Aceh Besar Regency: PELATIHAN PEMBUATAN VIRGIN COCONUT OIL (VCO) METODE PENGASAMAN DI GAMPONG LAMBRO DEYAH KECAMATAN KUTA BARO KABUPATEN ACEH BESAR - Endiyani; Surya Darma; Sri Agustina; Maghfirah; Ika Rezvani Aprita; Irhami; Chairil Anwar; Zulvia Maika Letis; Mizar Liyanda (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2024)
Virgin Coconut Oil (VCO) is a modification of the coconut oil making process so that a product with low water content and free fatty acid content is produced, clear in color, smells good, and has a long shelf life of more than 12 months. This community service activity aims to conduct training in making Virgin Coconut Oil (VCO) using the acidification method in Gampong Lambro Deyah, Kuta Baro district, Aceh Besar Regency. The community gained more knowledge about how to utilize agricultural commodity products, namely coconut and utilize coconut milk into other more useful products, namely VCO. The community of Gampong Lambro Deyah is very enthusiastic and interested in re-processing coconut in the form of coconut milk into Virgin Coconut Oil (VCO) so that residents' knowledge becomes more developed, and the results of the VCO can be used personally or marketed and can increase family income